Incentivizing Change Within Social Determinants of Health Using Blockchain Technology - McFarlane, Chrissa; Finch, Marquesa; Gray, Tiffany R.; Fuchs, Jonathan M.; Hersh, William; Clouse, John (Frontiers in Blockchain, 2020)
There are growing initiatives and calls for focusing greater attention to social determinants of health and their impact on population health [1]. Several emerging strategies are being used to begin to address social determinants, such as the use of health impact assessments and applying health in all policies (HiAP). These strategies and tools are being implemented in an effort to review existing and needed policies, as well as propose new policies to lessen health disparities [2]. Efforts to further integrate social determinants of health through the use of health information technology and other emerging technologies, such as distributed ledger technology both in and outside of existing health care systems are also increasing [2]. Understanding and addressing the social determinants of health through both traditional and non-traditional sectors is key to further reducing health disparities [1, 3-4]. Through exploration of the current state of social determinants of health in the healthcare industry, an analysis of blockchain technology will render the acceleration and adoption of social determinants of health to effectively provide improved health outcomes.